PBT (polybutylene terephthalate) composition as well as preparation method and application thereof
By combining PBT resins with different melting points and introducing specific additives, the problems of melting difficulties and warping of PBT materials in ultrasonic welding are solved, and high flame retardancy, fluidity and excellent ultrasonic welding performance are achieved.
Patent Information
- Application Number
- CN202411538105.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-31
AI Technical Summary
PBT materials have melting difficulties and warping during ultrasonic welding, which affects welding quality and inorganic materials reduce ultrasonic welding performance.
By combining PBT resins with different melting points, combining organic solid phosphate and suborganic halogen-free flame retardant, a specific ultrasonic welding modifier and short-length glass fiber are introduced to optimize the flame retardancy, fluidity and ultrasonic welding performance of the product. .
The flame retardancy and machining fluidity of ultra-thin size are achieved, which significantly improves the ultrasonic welding effect and comprehensive performance, and the pull-off force reaches more than 170N.
Smart Images

Figure BDA0005112078540000071 
Figure BDA0005112078540000081 
Figure BDA0005112078540000082
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer materials, and in particular to a PBT composition and a preparation method and application thereof. Background Art
[0002] In addition to requiring sufficient flame retardancy and processing performance to meet production and use requirements, plastic parts used in the electrical and electronic industry also need to have ultrasonic welding performance because they often need to be processed using ultrasonic welding.
[0003] Ultrasonic welding is a process of welding plastic products by ultrasonic method. It is often used in the production of small electrical components such as charger housings, USB connectors, low-voltage electrical housings, etc. Among them, one of the factors that affect the welding quality is the type of welding plastic. For example, the PBT (polybutylene terephthalate) material commonly used in the electrical industry has good mechanical strength and processing properties, but it is a fast crystallizing material. It is difficult for the welding surface to melt in the solid state, and it is necessary to extend the welding time or perform pressurization operations. On the other hand, due to the large difference in shrinkage rate between the injection molding flow direction and the vertical direction of the PBT material, a large degree of warping will occur in the preparation of some lightweight products, which seriously affects the ultrasonic welding.
[0004] In addition, the inorganic materials present in PBT materials will also reduce their ultrasonic welding performance. Summary of the invention
[0005] Based on the defects of the prior art, the purpose of the present invention is to provide a PBT composition. The product is compounded by two PBT matrix resins with different melting points, and organic solid phosphate is combined with a secondary organic halogen-free flame retardant as a flame retardant component, and an ultrasonic welding modifier of a specific composition is introduced for synergy, so as to achieve ultra-thin size flame retardancy, processable fluidity, and excellent ultrasonic welding effect.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] A PBT composition comprising the following components in parts by weight:
[0008] PBT resin 1 30-45 parts, PBT resin 2 8-15 parts, organic halogen-free flame retardant 8-16 parts, phosphate ester 3-7 parts, ultrasonic welding modifier 1-4 parts, glass fiber 20-35 parts;
[0009] The melting point of the PBT resin 1 is 220-235° C., and the melting point of the PBT resin 2 is ≤200° C.;
[0010] The melting point of the phosphate ester is ≥90°C;
[0011] The ultrasonic welding modifier includes a polyether block amide elastomer;
[0012] The length of the glass fiber is ≤100 μm.
[0013] Preferably, the mass ratio of the PBT resin 1 to the PBT resin 2 is (2.1-4.9):1.
[0014] Preferably, the mass ratio of the PBT resin 1 to the PBT resin 2 is in the range of one or any two of 2.1:1, 2.3:1, 2.5:1, 2.8:1, 2.9:1, 3:1, 3.5:1, 3.7:1, 4:1, 4.5:1, and 4.9:1.
[0015] More preferably, the mass ratio of the PBT resin 1 to the PBT resin 2 is (2.9-3.7):1.
[0016] More preferably, the weight proportion of the PBT resin 1 is 35 to 27 parts, and the weight proportion of the PBT resin 2 is 10 to 12 parts.
[0017] Further preferably, the weight portion of the ultrasonic welding modifier is 2 to 3 parts.
[0018] Preferably, in the PBT composition, the sum of the total mass contents of PBT resin 1 and PBT resin 2 is ≥50wt%.
[0019] Conventional PBT resin has a high melting point, fast crystallization rate, and high degree of crystallization, so it has good heat resistance, but it is difficult to effectively process using conventional ultrasonic welding technology. On the other hand, in order to meet basic usage requirements, PBT materials are also compounded with functional additives such as fillers and flame retardants during processing. If there are more inorganic components in these additives, the ultrasonic welding efficiency of the product will also be reduced. Based on this, in the technical solution of the present invention, PBT resins with different melting points are used for compounding. The high-melting-point PBT resin 1 maintains the basic mechanical strength requirements, while the low-melting-point PBT resin effectively reduces the melting energy consumption of the overall matrix resin, widens the process window of ultrasonic welding, increases the fluidity of the product, and ultimately improves the ultrasonic welding performance of the product; on the other hand, in the technical solution of the present invention, pure organic flame retardants and specific short-length glass fibers are used as functional auxiliary ingredients. On the one hand, the phosphate ester with a specific melting point is solid at room temperature, and can be melted and plasticized in the processing temperature zone. The ultrasonic welding performance is far superior to other inorganic or organic flame retardant synergists without affecting the fluidity and flame retardancy. On the other hand, the ultra-short glass fiber has better dispersion and thermal conductivity in the product, and a low degree of anisotropy, which can fully guarantee the ultrasonic welding performance of the product and basically does not affect the mechanical properties of the product. After optimizing the design of the main resin and functional additives, the technical solution of the present invention also uses a PA elastomer with polyamide as the hard segment and polyether as the soft segment as an ultrasonic welding modifier for synergistic compounding. This component has high compatibility with the PBT resin and can further improve the toughness of the product. At the same time, after the resin is melted, it can effectively combine with it and improve its ultrasonic welding performance, so that the product has sufficient pull-off force during the welding process.
[0020] Through the coordinated use of these components, the product not only achieves high flame retardant performance in a light and thin size, but also has good fluidity, good ultrasonic welding effect and excellent comprehensive performance. If other types or conventional similar components are used to replace them, the performance of the product will be greatly reduced. In addition, the product ratio of each component is also the key to the product achieving the expected performance. For example, if the addition ratio of PBT resin 2 is too small, the fluidity of the product is poor and the ultrasonic welding effect is also poor. However, if it is added too much, the crystallinity of the product will be significantly reduced, the mechanical strength of the product will be poor and the injection molding effect will be poor.
[0021] Preferably, the intrinsic viscosity of the PBT resin 1 at 25° C. is 0.8 to 0.9 dL / g.
[0022] More preferably, the melting point of the PBT resin 1 is in the range of one or any two of 220°C, 222°C, 223°C, 225°C, and 228°C.
[0023] Preferably, the intrinsic viscosity of the PBT resin 2 at 25° C. is 0.8 to 0.95 dL / g.
[0024] More preferably, the melting point of the PBT resin 2 is 160-200°C, more preferably 175-195°C, more preferably, the melting point of the PBT resin 2 is in the range of one or any two of 175°C, 185°C, 190°C, 192°C, 195°C, 198°C, and 200°C.
[0025] Preferably, the organic halogen-free flame retardant is a hypophosphite flame retardant.
[0026] Preferably, the phosphate ester is at least one of 1,3-phenylene phosphate tetrakis(2,6-dimethylphenyl) ester and hydroquinone bis(diphenyl phosphate), and the melting point is 92-110°C.
[0027] The high melting point phosphate ester of the present invention contains a phosphorus-oxygen double bond, and thus can improve the stability of the hypophosphite flame retardant in the resin matrix to a certain extent, so that it can fully exert its flame retardant properties, while improving the uniformity and flame retardancy of the components of the overall product in a light and thin design.
[0028] Preferably, the average diameter of the glass fiber is 10-15 μm.
[0029] Preferably, the average length of the glass fibers is 50-80 μm.
[0030] The average diameter and average length of the glass fiber of the present invention are tested by a two-dimensional microscope method, and the specific method is: ultrasonically disperse the glass fiber in anhydrous ethanol, then screen at least 200 glass fiber monofilaments under a two-dimensional microscope, and use image mapping software to confirm the diameter and length, and the statistical average value is the average diameter and average length of the glass fiber.
[0031] Preferably, the ultrasonic welding modifier is a nylon 6 elastomer.
[0032] Preferably, the density of the ultrasonic welding modifier is 1.0-1.2 g / cm 3 .
[0033] Preferably, the Shore hardness of the ultrasonic welding modifier is 40D-55D.
[0034] Preferably, the components of the PBT composition further include 2 to 4 parts of a toughening agent.
[0035] More preferably, the toughening agent is at least one of ethylene-methyl acrylate-glycidyl methacrylate terpolymer and ethylene-butyl acrylate-glycidyl methacrylate terpolymer.
[0036] By introducing a specific amount of toughening agent into the product, the mechanical strength of the product can be further improved, so that it can exhibit stronger pull-off force during ultrasonic welding.
[0037] Preferably, the components of the PBT composition further include 0.5 to 1.5 parts of a lubricant.
[0038] More preferably, the lubricant is at least one of an ester lubricant, an amide lubricant, and an oxidized polyethylene lubricant.
[0039] More preferably, the lubricant is an oxidized polyethylene lubricant, and the melting point of the oxidized polyethylene lubricant is 90-110°C.
[0040] When the oxidized polyethylene lubricant is used in the PBT composition of the present invention, on the one hand, its lubricating effect can improve the external lubricity of the entire component, reduce the system viscosity of the product during processing, increase the fusion between the component and the resin, and further improve the ultrasonic welding effect of the product. On the other hand, this component can also have a synergistic effect with the polyether block amide elastomer, enhance the bonding effect of the compounded resin, and ultimately improve the ultrasonic welding performance of the product.
[0041] Preferably, the components of the PBT composition further include 0.1 to 0.3 parts of a chain extender.
[0042] More preferably, the chain extender is at least one of bisphenol A diglycidyl ether and 3,4-epoxycyclohexylmethyl-3',4'-epoxycyclohexanecarboxylate.
[0043] Further introducing a chain extender into the components of the PBT composition of the present invention can accelerate the combination of small molecules during product processing, reduce the degree of degradation of the components, and also increase the degree of molecular chain fusion of each component during ultrasonic welding, thereby improving the welding effect.
[0044] Preferably, the components of the PBT composition further include 0.1 to 0.3 parts of an antioxidant.
[0045] More preferably, the antioxidant is a hindered phenol antioxidant, more preferably at least one of β(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 1,3,5-tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl)-1,3,5-triazine-2,4,6-(1H,3H,5H)-trione.
[0046] More preferably, the components of the PBT composition may also include, but are not limited to, antistatic agents, light stabilizers, solvent resistance, etc. Based on the processing or actual use needs of the product by those skilled in the art, other types of functional additives may be added without affecting the expected performance of the product. For example, the above-mentioned additives may improve the antistatic ability, light aging resistance and solvent resistance of the product without affecting the flame retardancy, fluidity and ultrasonic welding performance of the product. In order to give the product color, those skilled in the art may also add a certain amount of colorant to the product. That is, the description of the components of the PBT composition in the technical solution of the present invention is not a limitation on its types.
[0047] Another object of the present invention is to provide a method for preparing the PBT composition, comprising the following steps:
[0048] The components are added into a screw extruder for melt extrusion and granulation to obtain the PBT composition.
[0049] Preferably, the temperature zones of the screw extruder are set to 200-230°C in zone one, 240-260°C in zone two, 235-255°C in zone three, 235-255°C in zone four, 235-255°C in zone five, 240-260°C in zone six, 240-260°C in zone seven, 220-240°C in zone eight, 220-240°C in zone nine, and 240-260°C in zone ten, and the screw speed is 200-450rpm.
[0050] Another object of the present invention is to provide application of the PBT composition in the preparation of electronic and electrical parts.
[0051] Preferably, the electronic and electrical components include at least one of a charger housing, a USB connector, and a low-voltage electrical appliance housing.
[0052] The PBT composition of the present invention is based on its composite dual-melting-point matrix resin, and simultaneously introduces a specific type of filler, a flame retardant system additive, and an ultrasonic welding modifier for synergistic effect. It can not only achieve high flowability under a lightweight design (0.4mm) while maintaining the flame retardancy of the product, but also significantly improve its ultrasonic welding performance compared to traditional PBT composite materials, and significantly improve the production efficiency and production quality when used in the production of electronic and electrical components with corresponding requirements, and the ultrasonic welding pull-off force reaches more than 170N.
[0053] The beneficial effect of the present invention is that the present invention provides a PBT composition, which is compounded by two PBT matrix resins with different melting points, and uses organic solid phosphate and sub-organic halogen-free flame retardant as flame retardant components, and introduces an ultrasonic welding modifier of a specific composition for synergistic effect, so as to achieve ultra-thin size flame retardancy, processable fluidity, and excellent ultrasonic welding effect. DETAILED DESCRIPTION
[0054] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present invention in detail, rather than to limit the present invention. All other embodiments obtained by those of ordinary skill in the art without making creative work premise belong to the protection scope of the present invention. The experimental reagents and instruments involved in the implementation of the present invention, unless otherwise specified, are all commonly used common reagents and instruments.
[0055] Examples 1 to 16
[0056] An embodiment of a PBT composition and a preparation method and application thereof according to the present invention, the components of the PBT composition are shown in Table 1.
[0057] The preparation method of the PBT composition comprises the following steps:
[0058] The components are mixed uniformly, and then melt-extruded and granulated in a twin-screw extruder to obtain the PBT composition.
[0059] When the components are melt-extruded, the temperature zones of the twin-screw extruder are set to 210°C for zone one, 245°C for zone two, 250°C for zone three, 250°C for zone four, 255°C for zone five, 250°C for zone six, 245°C for zone seven, 240°C for zone eight, 235°C for zone nine, and 240°C for zone ten, and the screw speed is 300rpm.
[0060] Comparative Examples 1 to 9
[0061] The difference between the comparative examples and the embodiments is only in the types and proportions of components, as shown in Table 2.
[0062] Among the components described in each embodiment and comparative example,
[0063] The PBT resin a is PBT GX112 produced by Yizheng Chemical Fiber, with a melting point of 233° C. and an intrinsic viscosity of 0.82 dL / g at 25° C.;
[0064] The PBT resin b is PBT GX112J produced by Yizheng Chemical Fiber, with a melting point of 223.2°C and an intrinsic viscosity of 0.85 dL / g at 25°C;
[0065] The PBT resin c is PBT DR905 produced by Yizheng Chemical Fiber, with a melting point of 190°C and an intrinsic viscosity of 0.894 dL / g at 25°C;
[0066] The PBT resin d is a homemade product, prepared according to the method described in Example 2 of CN109575252A, with a melting point of 186°C and an intrinsic viscosity of 0.838 dL / g at 25°C;
[0067] The organic halogen-free flame retardant is Exolit OP1230 produced by Clariant, a hypophosphite flame retardant;
[0068] The phosphate ester 1 is PX200 produced by Daihachi Chemical Industry Co., Ltd., 1,3-phenylene phosphate tetrakis (2,6-dimethylphenyl) ester, with a melting point of 95°C;
[0069] The phosphate ester 2 is WSFR-PX-220 produced by Zhejiang Wansheng, hydroquinone bis(diphenyl phosphate), with a melting point of 92°C;
[0070] The phosphate ester 3 is triphenyl phosphate produced by Shanghai Zhuhui New Materials Co., Ltd., with a melting point of 49.9°C;
[0071] The melamine polyphosphate is melamine cyanurate produced by Sichuan Fine Chemical Research and Design Institute;
[0072] The ultrasonic welding modifier 1 is produced by Arkema, France MH 2030, polyether block amide elastomer, density 1.14 g / cm 3 , Shore hardness 40D;
[0073] The ultrasonic welding modifier 2 is produced by Arkema, France 55R53SP 01, polyether block amide elastomer, density 1.03g / cm 3 , Shore hardness 52D;
[0074] The ultrasonic welding modifier 3 is NEUSoft produced by Arkema, France TM UR842A Natural, polyether block polyurethane elastomer, density 0.948g / cm 3 , Shore hardness 42A;
[0075] The glass fiber 1 is MF 7904 produced by Lanxess, Germany, with a length of ≤100 μm, an average length of 50 μm, and an average diameter of 14 μm;
[0076] The glass fiber 2 is EPH 80M-01N produced by Nippon Electric Glass Co., Ltd., with a length of ≤100 μm, an average length of 80 μm, and an average diameter of 10.5 μm;
[0077] The glass fiber 3 is MF 7980 produced by Lanxess, Germany, with a length of more than 100 μm, an average length of 190 μm, and an average diameter of 14 μm;
[0078] The glass fiber 4 is MF 7982 produced by Lanxess, Germany, with a length of more than 100 μm, an average length of 210 μm, and an average diameter of 14 μm;
[0079] The toughening agent is AX8900 produced by Arkema of France, ethylene-methyl acrylate-glycidyl methacrylate terpolymer;
[0080] The lubricant 1 is PED 521 produced by Clariant, an oxidized polyethylene wax type lubricant with a melting point of 103°C;
[0081] The lubricant 2 is PETS-AP produced by Italy Faji, an ester lubricant with a melting point of 60°C;
[0082] The lubricant 3 is EBS B50 produced by Guangzhou Runfeng Chemical, an amide lubricant with a melting point of 142°C;
[0083] The chain extender is commercially available bisphenol A diglycidyl ether;
[0084] The antioxidant is commercially available 1,3,5-tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl)-1,3,5-triazine-2,4,6-(1H,3H,5H)-trione.
[0085] Unless otherwise specified, the components and raw materials used in the embodiments and comparative examples of the present invention are all commercially available raw materials, and the components and raw materials used in each parallel experiment are all of the same kind.
[0086] Table 1
[0087]
[0088]
[0089] Table 2
[0090]
[0091] In order to verify the performance of the PBT composition of the present invention, the products prepared in each embodiment and comparative example were subjected to the following performance tests, and the specific steps are as follows:
[0092] (1) Flame retardant performance test: The products of each embodiment and comparative example were injection molded into thin vertical strips of 127*13*0.8 mm and 127*13*0.4 mm, and the flame retardant grade was tested according to the UL94-2020 standard;
[0093] (2) Fluidity test: The spiral length of each product was measured at a temperature of 260°C and a pressure of 80 MPa. 51 films were continuously injected and the spiral length of the last mold product was tested. The longer the length, the better the fluidity of the product.
[0094] (3) Ultrasonic welding performance test: Each product was injection molded into a 80*10*4 mm specimen for ultrasonic welding. The welding area was 10*10 mm, the pressure was 20 MPa, the welding time was 0.5 s, and the pressure was maintained for 1 s. Subsequently, a tensile testing machine was used to perform a pull-off force test of the ultrasonic welding strength. The greater the pull-off force, the better the ultrasonic welding performance.
[0095] The test results are shown in Tables 3 and 4.
[0096] Table 3
[0097]
[0098] Table 4
[0099]
[0100] It can be seen from Table 3 and Table 4 that the PBT composition of the present invention has ideal comprehensive performance. The flame retardant grade of the product can reach V0 at a thickness of 0.8 mm, and can reach V2 at a thinner thickness of 0.4 mm, with excellent flame retardant performance. At the same time, the spiral line length of the product can reach more than 290 mm, which fully demonstrates that the product has considerable fluidity and excellent processing performance. In terms of ultrasonic welding performance, the pull-off force of the product after welding using a conventional ultrasonic welding process can reach 170N or more.
[0101] According to Comparative Examples 1-2 and Examples 1, 4-6, and 10-11, it can be seen that the two PBT resins with different melting points have greatly improved fluidity and ultrasonic welding performance when compounded. When the total amount of PBT resin added remains unchanged, if the PBT resin with a low melting point is not used for compounding, as shown in Comparative Example 1, although the flame retardant performance of the product is not affected, the spiral length and the pull-off force are not up to standard; as the compounding amount of the low-melting-point PBT resin increases, the fluidity and ultrasonic welding performance of the product are gradually improved, but after reaching a certain level, the crystallization performance of the product will decrease, which not only affects the ultrasonic welding performance, but even affects the flame retardancy of the product due to molding problems, as shown in Comparative Example 2. When the ratio of the two resins is in the range of (2.9-3.7):1, the corresponding products of Examples 1 and 5 have better comprehensive performance.
[0102] On the other hand, the use of ultrasonic welding modifier in the product of the technical solution of the present invention is also the key to making the product have ideal ultrasonic welding performance. As can be seen from Example 1, Example 12 and Comparative Example 7, when selecting its type, if other commercially available types other than polyether block amide elastomers are selected, the product will not be able to achieve the expected improvement effect, and the pull-off force after ultrasonic welding is low. According to Example 1, Examples 7 to 9 and Comparative Examples 5 to 6, it can be seen that when the amount added is small, the product not only has low mechanical strength, but also the compatibility and dispersibility of the components are not ideal, and ultrasonic welding cannot be effectively performed. As shown in Comparative Example 5, although its fluidity is relatively high, its pull-off force is low, and it even shows a low level in flame retardancy. As the amount of ultrasonic welding modifier added increases, the fluidity of the product gradually decreases, and as a result, the flame retardant properties of the product and the pull-off force after ultrasonic welding are significantly improved. When the amount added is 1 to 4 parts, the product can achieve high flame retardancy and high ultrasonic weldability while ensuring sufficient fluidity. However, if the amount added is too much, as shown in Comparative Example 6, the fluidity of the product is poor, affecting the uniformity of the product components, the flame retardancy of the product decreases, and the pull-off force is also reduced to a level similar to that of Comparative Example 5.
[0103] In addition to key additives, the selection of flame retardant synergists and fillers in the product will also have a decisive influence on its performance. As shown in Example 1, Example 12, and Comparative Examples 3-4, there are many types of existing phosphoric acid synergists used as flame retardant synergists. However, in the product system described in the present invention, if non-phosphate ester phosphate synergists or low-melting-point phosphate ester synergists are used, they cannot work together with ultrasonic welding modifiers and low-melting-point PBT resins to improve the fluidity and ultrasonic welding effect of the product. For example, by comparing Example 1, Example 13 and Comparative Examples 8-9, it can be seen that in the product described in the present invention, if longer glass fibers are used, the degree of heterogeneity of each phase is large, which reduces its dispersibility in the product, and the product cannot obtain ideal fluidity and ultrasonic welding performance.
[0104] It can be seen from Example 1 and Examples 14 to 15 that when different lubricants are used, the performance of the product is somewhat different. When an oxidized polyethylene lubricant is used in combination, it can produce a synergistic effect with the ultrasonic welding modifier to increase the bonding effect of the resin component, thereby further improving the pull-off force of the product.
[0105] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A PBT composition, characterized in that: The composition comprises the following components in parts by weight: PBT resin 1 30-45 parts, PBT resin 2 8-15 parts, organic halogen-free flame retardant 8-16 parts, phosphate ester 3-7 parts, ultrasonic welding modifier 1-4 parts, glass fiber 20-35 parts; The melting point of the PBT resin 1 is 220-235° C., and the melting point of the PBT resin 2 is ≤200° C.; The melting point of the phosphate ester is ≥90°C; The ultrasonic welding modifier includes a polyether block amide elastomer; The length of the glass fiber is ≤100 μm.
2. The PBT composition according to claim 1, characterized in that: The mass ratio of the PBT resin 1 to the PBT resin 2 is (2.1-4.9):
1.
3. The PBT composition according to claim 1, characterized in that: The components of the PBT composition also include 2 to 4 parts of a toughening agent.
4. The PBT composition according to claim 1, characterized in that: The toughening agent is at least one of ethylene-methyl acrylate-glycidyl methacrylate terpolymer and ethylene-butyl acrylate-glycidyl methacrylate terpolymer.
5. The PBT composition according to claim 1, characterized in that: The components of the PBT composition also include 0.5 to 1.5 parts of a lubricant.
6. The PBT composition according to claim 5, characterized in that: The lubricant is at least one of an ester lubricant, an amide lubricant, and an oxidized polyethylene lubricant.
7. The PBT composition according to claim 1, characterized in that: The components of the PBT composition also include 0.1 to 0.3 parts of a chain extender and / or 0.1 to 0.3 parts of an antioxidant; preferably, the chain extender is at least one of bisphenol A diglycidyl ether and 3,4-epoxycyclohexylmethyl-3',4'-epoxycyclohexanecarboxylate; and the antioxidant is a hindered phenol antioxidant.
8. The method for preparing the PBT composition according to any one of claims 1 to 7, characterized in that: The following steps are involved: Adding each component into a screw extruder for melt extrusion and granulation to obtain the PBT composition; Preferably, the temperature zones of the screw extruder are set to 200-230°C in zone one, 240-260°C in zone two, 235-255°C in zone three, 235-255°C in zone four, 235-255°C in zone five, 240-260°C in zone six, 240-260°C in zone seven, 220-240°C in zone eight, 220-240°C in zone nine, and 240-260°C in zone ten, and the screw speed is 200-450rpm.
9. Use of the PBT composition according to any one of claims 1 to 7 in the preparation of electronic and electrical parts.
10. The use according to claim 9, characterized in that The electronic and electrical components include at least one of a charger housing, a USB connector, and a low-voltage electrical housing.
Citation Information
Patent Citations
Preparation method of low-melting-point PBT copolyester
CN109575252A
Casing for electronic equipment
CN104520380A
High-toughness and high-fluidity thin-wall flame-retardant PBT (polybutylene terephthalate) composition as well as preparation method and application thereof
CN116285237A
PBT / PC alloy with stable mechanical properties, and preparation method therefor and article thereof
WO2023279984A1